TWO HUNDRED FACTORS OF MELANOIDINE MAKING REACTIONS - Eduard Ervandovich Khachaturian; Tatyana Sergeyevna Gvasaliya; Tatyana Petrovna Yakimenko (Современная наука и инновации)
Melanoidins proceeds readily when heated with sucrose to 100 amino acids 0C or higher. It is observed in the heat-treated products, both animal and vegetable origin. Melanoidins formed a crust on the surface of the products during the roasting, baking, give the color of melted milk, broth, define a dark color digested jam and fruit-berry puree.